Comparing clinical and imaging features of patients with MOG antibody-positivity and with and without oligoclonal bands - Tomizawa, Yuji; Hoshino, Yasunobu; Kamo, Ryota; Cossu, Davide; Yokoyama, Kazumasa; Hattori, Nobutaka (Frontiers in Immunology, 2023)
Introduction: Myelin-oligodendrocyte glycoprotein antibody (MOG)-associated disorder (MOGAD) is a recently identified immune-mediated inflammatory disorder of the central nervous system (CNS). The significance of oligoclonal bands (OCBs) is not fully elucidated. This study investigated the clinical differences between patients with MOGAD who tested positive or negative for OCBs.The study was conducted on 23 patients with MOG-IgG-seropositivity who presented with central nervous system (CNS) symptoms. The patients were screened and divided into OCB-positive (n=10) and OCB-negative (n=13) groups, and their demographic, clinical, and magnetic resonance imaging (MRI) features were compared.The results revealed that patients with OCB-positivity had a significantly higher frequency of relapse, and their IgG index was significantly higher. Discussion: OCBs were common in MOGAD met the consensus criteria. The study concluded that careful treatment decision-making is necessary in MOG antibody-positive cases with OCB-positivity.